Effect of NPK Phonska Fertilizer Dose and Silica Fertilizer Concentration on Garlic (Allium sativum L.) - Choirina Kamilia Rohani; Makhziah Makhziah; Djarwatiningsih Djarwatiningsih (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Garlic is widely recognized for its culinary, industrial, and medicinal applications, attributed to its sulfur compounds and allicin, which contribute to its pungent taste and distinctive aroma. This study, conducted in Sajen Village, Pacet District, Mojokerto, from January to May 2024, aimed to evaluate the effects of Phonska NPK and silica fertilizers on garlic production. A factorial experimental design with two factors was employed using a Split-Plot Design within a Randomized Complete Block Design (RCBD). The main plots were treated with silica fertilizer at concentrations of 0 g/L, 5 g/L, 10 g/L, and 15 g/L, while the subplots received Phonska NPK fertilizer at rates of 0 kg/ha (control), 400 kg/ha, 600 kg/ha, and 800 kg/ha. Data were analyzed using analysis of variance (ANOVA) and the HSD test at a 5% significance level. Results indicated that the combination of 0 g/L silica fertilizer and 800 kg/ha Phonska NPK fertilizer yielded the highest garlic production. Although the individual application of Phonska NPK fertilizer did not have a significant effect, the absence of silica fertilizer (0 g/L) significantly influenced leaf width and the development of generative structures. Keywords: Harvest, Nutrient, Potassium, Tuber size.